KURS RUPIAH, INDEKS NIKKEI 225, BI RATE, DAN PENGARUHNYA TERHADAP STOCK EXCHANGE INDEKS HARGA SAHAM GABUNGAN (IHSG) PERIODE TAHUN 2018-2020 - Andini Nurwulandari (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
Gross Domestic Product (GDP) growth is a constructive indicator and vice versa. A rise in GDP affects the buying power of citizens positively. It will therefore raise demand for the commodity. A surge in the market for goods raises the firm's earnings and may also increase the stock price. The analysis was designed to examine the impact on composite stock price index using data from time series from January 2018 to December 2020 of Rupiah Exchange rate, Nikkei 225 Index, and BI Rate. Multiple linear regression is used in the mixed Stock Price Index scheme to identify the relevant influence of BI on the Rupiah and Nikkei 225. The test results show that the BI rate has a significant positive effect on the Rupiah exchange rate for the composite stock pricing index. Meanwhile, the Nikkei 225 Index has no impact on the Composite Stock Price Index.